How gut transcriptional function of Drosophila melanogaster varies with the presence and composition of the gut microbiota. Issue 8 (2nd December 2017) - Bost, Alyssa; Franzenburg, Soeren; Adair, Karen L.; Martinson, Vincent G.; Loeb, Greg; Douglas, Angela E.
Abstract: Despite evidence from laboratory experiments that perturbation of the gut microbiota affects many traits of the animal host, our understanding of the effect of variation in microbiota composition on animals in natural populations is very limited. The core purpose of this study on the fruit fly Drosophila melanogaster was to identify the impact of natural variation in the taxonomic composition of gut bacterial communities on host traits, with the gut transcriptome as a molecular index of microbiota‐responsive host traits. Use of the gut transcriptome was validated by demonstrating significant transcriptional differences between the guts of laboratory flies colonized with bacteria and maintained under axenic conditions. Wild Drosophila from six field collections made over two years had gut bacterial communities of diverse composition, dominated to varying extents by Acetobacteraceae and Enterobacteriaceae. The gut transcriptomes also varied among collections and differed markedly from those of laboratory flies. However, no overall relationship between variation in the wild fly transcriptome and taxonomic composition of the gut microbiota was evident at all taxonomic scales of bacteria tested for both individual fly genes and functional categories in Gene Ontology. We conclude that the interaction between microbiota composition and host functional traits may be confounded by uncontrolled variation in both ecological circumstance and host traits (e.g., genotype, age physiological condition) under natural conditions, and that microbiota effects on host traits identified in the laboratory should, therefore, be extrapolated to field population with great caution.